Role of visual inspection of cervix with acetic acid and high risk human papilloma virus DNA testing in screening for cervical cancer - Gami, Neha; Gandhi, Gauri; Batra, Swaraj; Zutshi, Vijay; Das, B. C.; Bhambhani, Suresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To evaluate the role of VIA alone and in combination with high risk Human Papilloma virus DNA testing as a screening test for cervical dysplasia and cancer. Methods: 400 symptomatic patients from the gynecology outpatient department were screened using Pap smear and VIA. HPV DNA testing was done for 62 VIA positive and 100 VIA negative women. Colposcopy was done for all women. Those found positive on any or all of the screening tests were subjected to cervical biopsy. The results were analysed for PAP, VIA, HPV and a combined test using VIA and HPV both. Results: VIA had the highest sensitivity (91%) to detect any grade of dysplasia. The sensitivity of the combination test (VIA + HPV) was 80.6% which was lower than that of VIA (91%) and also lower than that of HR HPV DNA detection (86%). The specificity of the combination test (VIA + HPV) was 68.3 % which was significantly higher than that of VIA alone (39%) (p = 0.000) and also higher than that for HPV DNA detection when used alone (56%). Pap smear had the highest specificity (95.12 %) but sensitivity was much lower at 52.7 %. Conclusions: VIA is a highly sensitive screening test. The main disadvantage is its low specificity. However the combination test of VIA + HR HPV testing overcomes this and at the same time maintains a high sensitivity. Thus a test which combines VIA plus HR HPV testing is better screening method than either of the three tests (VIA, HPV, PAP) done alone.